Inequality, income dynamics, and transitions of Mexican workers - Daniela Puggioni; Mariana Calderón; Alfonso Cebreros; León Fernández Bujanda; José A. Inguanzo; David Jaume (Banco de México, 2022)
We characterize the salient features of the distribution of earnings and earnings changes of formal workers in Mexico using social security records for the period 2005-2019. We find strong evidence of deviations from normality of these distributions. Comparing the results obtained with administrative data and household survey data suggests that this latter source of information is inadequate to fully capture the evolution of inequality and the properties of earnings changes. We also study the impact of transitions out of and back into formal employment on wages earned in the formal sector and the effect of early exposure to informality on future earnings. We document that workers who exit formal employment experience a significant wage penalty upon re-entry and that having the first job in the informal sector has a negative and significant impact on future earnings.
Keywords: E24; J24; J31; J46; 330; Earnings dynamics; higher-order earnings risk; inequality; worker transitions; informal labor markets